Impact of Surface Ozone on Wheat Yield in Selected Districts of Rajasthan (India): A Comparative Analysis of Concentration and Flux-Based Metrics - Naziya Tarannum; Nathan Booth; Nivedita Chaudhary (International Journal of Plant Production, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Skeletal muscle atrophy induced by aging and disuse atrophy are strongly associated with the upregulation of the endoplasmic stress protein CHOP in rats - J. Max Michel; Joshua S. Godwin; Nathan R. Kerr; Thomas E. Childs; Frank W. Booth; C. Brooks Mobley; David C. Hughes; Michael D. Roberts (Molecular Biology Reports, 2025)
Background While canonical anabolic and proteolytic pathways have been well examined in the context of skeletal muscle proteostasis, the roles of endoplasmic reticulum stress (ERS) and the induced unfolded protein response (UPR) are underappreciated. Thus, we aimed to determine whether aging and/or disuse atrophy in rats altered skeletal muscle ERS/UPR markers. Methods and Results Soleus (SOL) and plantaris (PLT) muscles of 3-month-old (mo), 6 mo, 12 mo, 18 mo, and 24 mo rats (9–10 per group, 48 in total) were analyzed for UPR proteins with further analysis performed on the protein CHOP. The gastrocnemius muscles of 4 mo rats that had undergone hindlimb immobilization (HLI, n = 12) or sham casting (CTL, n = 12) were analyzed for similar targets as well as more extensive CHOP-related targets. CHOP protein was greater in the PLT and SOL of 18 and 24 mo rats versus other age groups ( P < 0.05). Moreover, negative correlations existed between CHOP expression and normalized PLT ( R =-0.702, P < 0.001) and SOL ( R =-0.658, P < 0.001) muscle weights in all rats analyzed at different ages. CHOP protein expression was also greater in the gastrocnemius of HLI versus CTL rats ( P < 0.001), and a negative correlation existed between CHOP protein expression and normalized muscle weights in these rats ( R =-0.814, P < 0.001). Nuclear CHOP protein levels ( P < 0.010) and genes transcriptionally regulated by CHOP were also greater in HLI versus CTL rats ( P < 0.001) implicating transcriptional activity of CHOP is elevated during disuse atrophy. Conclusions CHOP is operative during aging- and disuse-induced skeletal muscle atrophy in rodents, and more research is needed to determine if CHOP is a key mechanistic driver of these processes.

Assessing the spatio-temporal tropospheric ozone and drought impacts on leaf growth and grain yield of wheat across Europe through crop modeling and remote sensing data - Thuy Huu Nguyen; Giovanni Alessandro Cappelli; Lisa Emberson; Gonzalez Fernandez Ignacio; Anisoara Irimescu; Savian Francesco; Ginaldi Fabrizio; Nathan Booth; George Boldeanu; Victoria Bermejo; Sam Bland; Michael Frei; et al. (European Journal of Agronomy, 2024)

Preparing for climate change in Washington State - Lara C. Whitely Binder; Jennifer Krencicki Barcelos; Derek B. Booth; Meriel Darzen; Marketa McGuire Elsner; Richard Fenske; Thomas F. Graham; Alan F. Hamlet; John Hodges-Howell; J. Elizabeth Jackson; Catherine Karr; Patrick W. Keys; et al. (Climatic Change, 2010)